Urgensi Dakwah Kultural Tokoh Agama Pada Masyarakat Bajo Bungku Selatan Morowali - Mansur Mansur; Eci Eci; Asliah Zainal (Universitas Hamzanwadi, 2023)
This research aims to identify the forms of cultural da'wah carried out by religious figures and the implementation of cultural da'wah carried out by religious figures in the Bajo Morowali community in Central Sulawesi. The research method uses qualitative research, where the research data is collected through observation and interviews. This research resulted in the finding that the cultural preaching of religious figures from the Bajo Morowali community in Central Sulawesi was carried out at ceremonies celebrating major Islamic holidays such as the Prophet's birthday and commemoration of the Isra' Mi'raj of the Prophet Muhammad. The forms of cultural da'wah carried out by religious leaders in the Bajo Morowali community, Central Sulawesi, are Matangong Ruma' Bau (building a new house) and cultural da'wah in the Sandro traditional healing ritual.